Little Women; Or, Meg, Jo, Beth, and Amy - Alcott, Louisa May, 1832-1888; Merrill, Frank T., 1848-1923 (Salt Lake City, UT : Project Gutenberg, 2011)
"Little Women; Or, Meg, Jo, Beth, and Amy" by Louisa May Alcott is a coming-of-age novel published in 1868-1869. The story follows four sisters$1 (BMeg, Jo, Beth, and Amy March$1 (Bas they navigate the passage from childhood to womanhood in Civil War-era Massachusetts. Loosely based on Alcott's own family, the novel explores themes of domesticity, work, and love while depicting the joys and struggles of nineteenth-century women's lives. Through their adventures and challenges, the March sisters embody different aspects of young American womanhood. (This is an automatically generated summary.)s
Wikipedia page about this book: https://en.wikipedia.org/wiki/Little_Women
Release date is 2011-08-16
David Edwards, Ernest Schaal, Robert Homa, and the Online Distributed Proofreading Team
Keywords: Autobiographical fiction; Young women -- Fiction; Sisters -- Fiction; Domestic fiction; Family life -- New England -- Fiction; New England -- Fiction; Bildungsromans; Mothers and daughters -- Fiction; March family (Fictitious characters) -- Fiction